Xuetongsu attenuates synovial inflammation in rheumatoid arthritis by inhibiting the IL-23/IL-17/NF-κB inflammatory axis - Yuxin Chen; Yasi Deng; Hao Zheng; Hao Zheng; Bin Li; Yupei Yang; Juan Huang; Hanwen Yuan; Mengyun Wang; Wei Wang; Huanghe Yu (Frontiers in Pharmacology)
IntroductionPersistent synovial hyperplasia, a hallmark of rheumatoid arthritis (RA), can lead to joint deformities. During the pathogenesis of RA, the expression of IL-23 promotes Th17 cell proliferation and IL-17 production, which in turn upregulates TNF-α, IL-1β, and RANKL in RA fibroblast-like synovial cells (RAFLS), forming the IL-23/IL-17/NF-κB inflammatory signaling axis, which further exacerbates synovial inflammation and joint destruction. Therefore, inhibiting the IL-23/IL-17/NF-κB inflammatory signaling axis may help alleviate synovial inflammation and could be a promising approach for treating RA. In our previous studies, we found a natural anti-inflammatory active component, Xuetongsu (XTS), which is the active ingredient in the Chinese Tujia ethnomedicine Xuetong, and it has shown significant effects in inhibiting the inflammatory proliferation of RAFLS.MethodsThe RAFLS model and adjuvant-induced arthritis (AIA) animal model were established, and silenced or overexpressed IL-23, and the anti-inflammatory mechanism of XTS was investigated using Western blotting and immunofluorescence. H&E staining was used to evaluate the efficacy of XTS in inhibiting RA synovial inflammatory hyperplasia. The anti-inflammatory and anti-RA bone destruction efficacy of XTS was evaluated by Masson's trichrome staining, Safranin O-Fast Green (SO-FG), Tartrate resistant acid phosphatase (TRAP) staining and radiological analysis. Blood and biochemical indices were used to evaluate the anti-inflammatory efficacy and safety of XTS.ResultsThe findings indicated that XTS exerted no notable influence on downstream molecular pathways such as IL-17 and NF-κB in RAFLS cells with silenced IL-23. However, in RAFLS cells with overexpressed IL-23 and in the RA rats model, XTS exhibited a clear inhibitory effect on the downstream factors, which demonstrated a certain dose-dependent relationship. Histopathological staining and radiological analysis showed that XTS could effectively alleviate foot paw swelling and improve synovial inflammatory hyperplasia and bone destruction in AIA rats. Blood analysis revealed that XTS was not only anti-inflammatory, but also improved haematopoiesis and provided hepatic and renal protection.DiscussionThese findings suggest that XTS targets IL-23 to inhibit the IL-23/IL-17/NF-κB axis, offering new insights into RA treatment. This study provides the first evidence that the natural product XTS exerts anti-inflammatory effects in RA by specifically targeting IL-23. Our findings reveal its molecular mechanism and establish a novel paradigm for developing IL-23-targeted RA therapies, advancing traditional medicine modernization.